UPAYA PENYELESAIAN KREDIT MACET PADA KREDIT USAHA RAKYAT DALAM PERJANJIAN PINJAM NAMA DITINJAU DARI PASAL 1873 KITAB UNDANG-UNDANG HUKUM PERDATA & UNDANG-UNDANG NO. 10 TAHUN 1998 TENTANG PERBANKAN : (Studi Studi Di PT. Bank Tabungan Negara, Tbk. KC Banyuwangi) - Monika Oktaviani, Diah; Pasaribu, Agnes; Brian Wicaksono, Demas (Fakultas Hukum Universitas 17 Agustus 1945 Banyuwangi, 2023)
Efforts to Settle Bad Loans on People's Business Loans Name Borrowing Agreement in terms of Article 1873 Civil Code & Law No. 10 Year 1998 About Banking (Research Study at PT. Bank Tabungan Negara, Tbk. KC Banyuwangi) Bank is one of the financial institutions in Indonesia. In Law Number 10 of 1998 concerning Banking, it is explained that a bank is a business institution that collects money from the public in the form of savings, then distributes it back to the community in the form of credit. In conducting loan transactions (credit) there is a binding agreement between the debtor and the creditor. However, the agreement made should not run in accordance with the validity of the provisions contained in the agreement. The credit agreement is made on behalf of. This action resulted in bad credit in credit loan transactions and had an impact on the debtor who lent his name, because the debtor must be responsible for what has been done. This is as explained in article 1873 of the Civil Code. With this event, it can lead to a default in the agreement made by the debtor with the creditor. The formulation of the problem in this thesis is (1) Is the people's business credit loan agreement on behalf of another person valid based on Article 1873 of the Civil Code? (2) What efforts can be made by Bank BTN in the settlement of bad loans on people's business loans using on behalf of other people? The research method used is an empirical research method in which the data obtained are based on the results of direct interviews with the Bank. Based on the results of research and discussion, the conclusions of this thesis are (1) In a people's business credit loan agreement on behalf of another person based on Article 1873 of the Civil Code, it can be said to be valid as long as it still fulfills the legal requirements of the agreement as described in Article 1320 of the Civil Code. Civil Law Act. (2) The settlement efforts carried out by Bank BTN in non-performing people's business loans on behalf of using amicable channels (consultation) to determine the payment process until it is paid off and obligations are fulfilled.